A content analysis study about stem education - (:unkn) unknown (Sakarya University, 2015)
The aim of this study is to evaluate the studies about STEM education in mathematics and science disciplines between the years of 2010-2015 through content analysis. For reviewing the reached studies five criteria were used: publication year, disciplines (mathematics, science, and science and mathematics), methodology (qualitative, quantitative and mixed), research areas, and participants. Articles which were accessed from internet in full text, especially were indexed in SSCI (Social Science Citation Index). A total of 51 articles were included in the research. STEM, STEM education, science and mathematics education search terms were used. The findings of the study provided that most studies conducted in 2014 and 23 articles were also related the teaching-learning research field. © The Turkish Online Journal of Educational Technology.
Keywords: Content analysis; Science and mathematics education; STEM education